New solution-processable carbazole derivatives as deep blue emitters for organic light-emitting diodes. Issue 11 (22nd January 2016) - Reig, Marta; Bubniene, Giedre; Cambarau, Werther; Jankauskas, Vygintas; Getautis, Vytautas; Palomares, Emilio; Martínez-Ferrero, Eugenia; Velasco, Dolores
Abstract : Triple bonds as π-spacers in deep blue carbazole-based emitters for non-doped organic light-emitting diodes. Abstract : Two new compounds based on three carbazole units connected by triple bonds as π-spacers have been developed as deep blue emitters for organic light-emitting diodes (OLEDs). Their optical and electrochemical properties were examined and their charge carrier transport properties were investigated by means of the xerographic time-of-flight (XTOF) technique. The prepared diodes demonstrate the feasibility of the new molecules as effective emitters in the deep blue region yielding devices with low turn-on voltages.